Pendampingan Pembelajaran Siswa Sekolah Dasar untuk Membentuk Kemandirian dan Kekuatan Literasi Masa Pandemi Covid-19 - Madjid, Abd.; M. Suud, Fitriah; Bahiroh, Siti (CV. Creative Tugu Pena, 2023)
Learning during the pandemic has had many effects on elementary school students, especially for low-grade students, namely grades one, two, and three. The survey results show that at Pendowoharja Elementary School there are some students who still cannot read well and are not able to be independent in learning. This is the reason for the servants of the Islamic Education Psychology program to hold a service with the theme of IT-based learning assistance at SD Muhammadiyah Pendowoharjo. The method used ABCD (Asset Based Community) to maximize the potential assets, which includes individual assets, communities, infrastructure, community, et al. This service is intended to increase students' interest and enthusiasm for learning and to make it easier for students to understand lessons, especially in reading problems. This community dedication is also carried out by providing ozonizer machines for schools in order to maintain health protocols so that students and parents feel comfortable when their children are at school. Learning takes place in shifts arranged by the teacher and students are invited according to a predetermined schedule. This mentoring activity makes students even more enthusiastic about learning and starting to be independent. Keywords: Learning Assistance Independence, Pandemic Period, Assistance Students